2018
DOI: 10.1111/ijd.14337
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic eruption of pregnancy in Mexico

Abstract: Background Currently, the exact incidence of Polymorphic Eruption of Pregnancy (PEP) in the Mexican population is unknown. PEP tends to manifest in the abdomen, primarily in the stretch marks caused by distension. It is characterized by severely pruritic urticarial-like papules that converge in plaques, extending to the buttocks and proximal thighs. Our study determined its incidence, along with other common dermatoses in pregnancy.Methods Patients between 14 and 45 years of age were evaluated. In each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…PUPPP actual incidence is not known, but one out of 130–300 pregnancies have been reported [ 22 ], and Elling et al [ 23 ] reported 1 in 200 single pregnancies (0.5%). Literature findings suggest that multiple pregnancies carry a greater risk of developing this skin condition, with an incidence of 2.9–16% in twin pregnancies and 14–17% in triplets [ 24 ]. PUPPP usually appears among primigravidae in the third trimester of pregnancy (with a mean onset of 35 weeks of gestation) or during the immediate postpartum period, with no tendency to relapse in subsequent pregnancies [ 21 , 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUPPP actual incidence is not known, but one out of 130–300 pregnancies have been reported [ 22 ], and Elling et al [ 23 ] reported 1 in 200 single pregnancies (0.5%). Literature findings suggest that multiple pregnancies carry a greater risk of developing this skin condition, with an incidence of 2.9–16% in twin pregnancies and 14–17% in triplets [ 24 ]. PUPPP usually appears among primigravidae in the third trimester of pregnancy (with a mean onset of 35 weeks of gestation) or during the immediate postpartum period, with no tendency to relapse in subsequent pregnancies [ 21 , 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors speculated that the third-trimester-aged placenta determines maternal fibroblast proliferation through released molecules known as F-substance [ 22 , 33 ]. Dominguez-Serrano et al [ 24 ] assumed a greater body mass index (BMI) could be associated with a higher risk of PUPPP [ 24 ]. Similarly, Ghazeeri et al [ 16 ] affirmed that 75% of PUPPP patients presented excessive maternal weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…PEP is also known as pruritic urticarial papules and plaques of pregnancy and is a benign self-limiting pruritic inflammatory disorder with an incidence of 1:120-1:300 pregnancies [25][26][27][28]. It usually occurs in the third trimester of pregnancy or immediately postpartum (in about 15% of cases) [8].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…[4][5][6] Although, the etiological cause of PEP remains unknown, evidence suggest a relationship between increased skin distension, cesarean deliveries, multiple gestation and male fetuses. [7][8] Clinical manifestation of PEP include intense pruritic erythematous papules arising within striae in the third trimester and/or postpartum period. The most common initial site are abdominal striae while the eruption can spread to the lower extremities, buttocks and chest.…”
Section: Introductionmentioning
confidence: 99%